Study of human papilomavírus infections in feminine sex patients, detected by hybrid capture assay in: survey of the cases - Carestiato, Fernanda N; Carvalho, Maria Odete O.; Ribeiro, Mariza O; Marinho, Mareia; Barbosa, Fábio M.; Silva, Licinio E.; Dimetz, Trude; Oliveira, Ledy H.S.; Cavalcanti, Silvia M.B. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Introduction: Although all the employed efforts the epidemies of Human Papillomavirus (HPV) still growing worldwide. Hence, the search for improvements in diagnosis of HPV infection is still necessary. Objective: To study the genital infections caused by the HPV. determining the prevalence of HPV types in female sex patients. attended at Laboratório Sérgio Franco of the State of Rio de Janeiro, in 2001. Mcthodology: 1.616 samples of female patients had been submitted the examinations for detection of HPV for the Technique of Hybrid Capture. Using the kit Digene (USA) Hybrid Capture® II HPV Test. Results: Among all the samples analyzed, 745 patients were infected by HPV (46.1%), against 871 negative results (53,9 %). In positive examinations. 436 were of high-risk group (Probe B), 64 of low-risk group (Probe A) and 245 were positive for both groups. The band of major prevalence of HPV infection was the 20-30 years of age. Conclusion: The results showed approximately 50% of the infected women, being the majority young women. Of these, more than 90% were infected with oncogenic HPV types (alone or in mixed infections), characterizing, a population with high risk to develop câncer and therefore, needs to be followed in order to preveni malignant transformation.